Experimental Study of Coarse Soil Properties Influencing Soil Abrasivity. (2016) - Sebastiani, Diego; Passeri, Daniele; Belardi, Girolamo; Miliziano, Salvatore
Abstract: The paper reports selected results of a study on tool wear for mechanized tunnelling in coarse soil. Several laboratory soil abrasion tests were performed and the results correlated with mineralogical composition, shape and surface roughness of the grains and the grain size curve of the soils. The analysis of the results clearly confirms the well-known correlation between soil abrasivity and quartz content and, for the soils tested, can quantify the relevant influence of grain size and grain roughness. We also report and discuss results useful for quantifying the positive effect of the addition of different chemical agents, injected as foams in a process known as soil conditioning, commonly performed in mechanized tunnel excavation using tunnel boring machines whit earth pressure technology to minimise tool consumption.